Construction of Ethno-Religious Identity in Nusa Tenggara Timur Local Politics - Yeheskial Adriaan Roen; Suharko Suharko; Muhammad Najib Azca (Political Science Program, Universitas Negeri Semarang, 2023)
This article described the discourse on ethnoreligious identity in electoral politics in NTT from the perspective of post-structuralism. The discursiveness of identity is important because it helps with how ethnoreligious identity is constructed to become hegemonic in electoral politics. Using Laclau and Mouffe’s discourse theory, this study found three articulations constructing ethnoreligious identity in electoral politics to become hegemonic, namely first, the historical articulation of enemy and ally; secondly, the institutionalization of representation of ethnoreligious identity in candidate pairs; and third, the daily socio-political practices of political actors. Reflectively, even though the three articulations have different working logics, they are ultimately absorbed in the “nodal point,” namely the hegemony of ethnoreligious identity in electoral politics. This study aims to raise citizens’ critical awareness that the hegemony of ethnoreligious identity in electoral politics is not taken for granted but is a social construction. By gaining this awareness, the citizens are expected not to be trapped in the essentialism of identity in electoral politics. This study contributes to the discourse study of the hegemony of ethno-religious identity in electoral politics.